Effect of anakinra on arthropathy in CINCA/NOMID syndrome - Kaneko Utako; Hara Ryoki; Kishi Takayuki; Kikuchi Masako; Nishimura Gen; Inaba Yutaka; Miyamae Takako; Shinoki Toshihiko; Imagawa Tomoyuki; Yokokta Shumpei (BMC, 2010)
Abstract CINCA/NOMID is an autoinflammatory disorder characterized by the triad of neonatal onset of cutaneous symptoms, chronic meningitis, and recurrent fever and it presents with distinctive osteoarthropathy, synovitis mainly of the large joints and overgrowth of epimetaphyseal cartilage, particularly of the long bones. The cartilage overgrowth eventually causes osseous overgrowth and deformity that persists beyond skeletal maturity and leads to limb length discrepancy, joint contracture, and early degenerative arthropathy. Autoinflammation in CAPS/NOMID has been proven to derive from excessive release of interleukin-1 (IL-1). It has been well documented that the IL-1 receptor antagonist anakinra (Kineret(R)) helps mitigate systemic inflammation in the disorder. However, a general consensus has not been reached on its beneficial effect on osteoarthropathy. The case of a girl with CINCA/NOMID syndrome who showed dramatic improvement of osteoarthropathy after anakinra treatment is reported. A 4-year-old girl suffered at the age of 10 months from a generalized urticarial skin lesion with recurrent episodes of fever and growth disorder. Blood examination revealed persistent massive neutrophilia, anemia and intense acute phase response. She manifested knee joint swelling with limited ROM when she was 20 months old and was diagnosed as being CINCA/NOMID based on characteristic findings of radiograph despite negative CIAS1 mutation. Radiological examination demonstrated metaphyseal fraying and cupping and widening of the growth plate in the distal femur. MR imaging showed mottled gadolinium enhancement at the chondrosseous junction. Neither significant joint effusion nor synovitis was identified. At 2 years and 7 months of age, anakinra, 2 mg/kg/day given by regular daily subcutaneous injections, was started. A few days after the initiation of the treatment, her clinical symptoms and laboratory findings of active inflammation were promptly alleviated. She was not able to walk unaided prior to the treatment, but she walked independently 1 month after the treatment. Follow-up radiographs and MR imaging showed that growth plate widening and gadolinium enhancement at the chondrosseous junction were less conspicuous. Furthermore, longitudinal growth of the femur and tibia was identified during 20 months of observation.